The Auditory System : Anatomy, Physiology, and Clinical Correlates, Second Edition. - Musiek, Frank E. (Plural Publishing, Incorporated, 2018)
This text is designed to provide comprehensive coverage of the anatomy and physiology of the central and peripheral auditory systems. Readers will benefit from the important link between science and clinical practice, with integrated clinical correlates found in each chapter. It is an essential text for graduate programs in audiology and a valuable reference for audiologists at any stage of their career.